Wheat Anaphylaxis in Adults Differs from Reactions to Other Types of Food - Kraft, Magdalena; Dölle-Bierke, Sabine; Renaudin, Jean Marie; Ruëff, Franziska; Scherer Hofmeier, Kathrin; Treudler, Regina; Pföhler, Claudia; Hawranek, Thomas; Poziomkowska-Gęsicka, Iwona; Jappe, Uta; Christoff, George; Müller, Sabine; et al. (The Journal of Allergy and Clinical Immunology: In Practice, 2021)
Background: Wheat is one of the most commonly consumed foods and a known elicitor of anaphylaxis in children and adults. Reactions in adults are often cofactor dependent and characterized by a prolonged time between food intake and the onset of symptoms making the diagnosis of wheat anaphylaxis challenging. Objective: To characterize a cohort of patients with the history of wheat anaphylaxis to better understand this atypical phenotype of anaphylaxis. Methods: Data from the European Anaphylaxis Registry from 2007 to 2019 (n = 10,636) including 250 patients (213 adults and 37 children) with a history of anaphylaxis caused by wheat were analyzed. Results: Wheat was the most common food elicitor of anaphylaxis in adults in the registry in Central Europe. Reactions to wheat in adults were frequently associated with exercise as a cofactor (82.8%) and partially delayed (57.5%). Only 36.9% of patients had atopic comorbidities, which was uncommonly low for adult patients allergic to other kinds of foods (63.2%). Anaphylaxis to wheat presented frequently with cardiovascular symptoms (86.7%) including severe symptoms such as loss of consciousness (41%) and less often with respiratory symptoms (53.6%). The reactions to wheat were more severe than reactions to other foods (odds ratio [OR] = 4.33), venom (OR = 1.58), or drugs (OR = 2.11). Conclusions: Wheat is a relevant elicitor of anaphylaxis in adults in Central Europe. Wheat anaphylaxis is highly dependent on the presence of cofactors and less frequently associated with atopic diseases compared with other food allergies. More data on mechanisms of wheat-induced anaphylaxis are required to develop preventive measures for this potentially life-threatening disease.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Anaphylactic reaction; Anaphylaxis; FDEIA; Food allergy; Omega-5-gliadin; Tri a 19; WDEIA; Wheat allergy; Wheat-dependent exercise-induced anaphylaxis